Descriptive studies on stylized facts of the German business cycle - Winfried Theis; Kai Vogtländer; Claus Weihs (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
Thirteen Stylized Facts of the german economy are studied with different descriptive statistical methods. The results of this study are considered with respect to other results from Project B3 Multivariate Bestimmung und Untersuchung von Konjunkturzyklen.
Keywords: 519; Konjunktur; Zeitreihenanalyse; Deskriptive Statistik; Deutschland